Healthy or diseased mouth? Representations of oral health in vulnerable populations. - Giselle Davis-Toledo (Universidad de Concepción., 2022)
Background: The society and the State must provide dental care and help prevent oral health problems by implementing public policies with cultural relevance that allow society to address and improve the inequity in health care that systematically affects people's well-being. The present study seeks to understand the representations of dental health in people who attend primary care services in vulnerable urban and rural areas of the central zone of Chile. Specifically, the representations of the causes, morbidities, and symptoms attributed to the healthy and diseased mouth. Material and Methods: A qualitative study based on the Grounded Theory was conducted, analyzing the social representations of oral health in a sample of 161 adult people receiving treatment at public primary care services and dental emergency units in rural and urban communes. Empirical saturation and triangulation by time, place, and subjects give reliability to the study. Results: The data obtained show that dental health is mainly valued for its implications for self-esteem and social integration. A naturalization of dental health problems is evidenced as an adaptive strategy to traditional access barriers, which is counterproductive with preventive strategies. Conclusion: The results of the study suggest the need to reinforce education in dental health implemented in a transversal manner, having aesthetic values and the population's expectations of sociability as the key to action.